2021
DOI: 10.1111/jzo.12876
|View full text |Cite
|
Sign up to set email alerts
|

Grasping behavior in the white‐tailed sea eagle (Accipitridae, Aves) explained by muscle architecture

Abstract: Hindlimbs of raptors play an essential role in feeding due to the grasping abilities that allow them to hunt and kill their prey. This study explores and quantifies for the first time the structural and mechanical features of the digit flexor muscles in one of the largest piscivorous European raptors, the white‐tailed sea eagle. We studied the myological architecture of nine muscles of five females and five males of Haliaeetus albicilla. We found that (1) reversed sexual dimorphism was not reflected in any of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Unlike previous studies (e.g., Mosto et al, 2021; Sustaita, 2008; Ward et al, 2002), we considered more individual muscles for allometric analysis and found 13 out of 14 were positively allometric, which implies that, with increasing body size, these specific muscles become much greater in PCSA and thus more force‐generation capacity in large‐bodied individuals. For the Eurasian sparrowhawk that shows significant RSD in body mass, the positive allometry indicated a potential for increasing force generation in females than expected for their body mass.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Unlike previous studies (e.g., Mosto et al, 2021; Sustaita, 2008; Ward et al, 2002), we considered more individual muscles for allometric analysis and found 13 out of 14 were positively allometric, which implies that, with increasing body size, these specific muscles become much greater in PCSA and thus more force‐generation capacity in large‐bodied individuals. For the Eurasian sparrowhawk that shows significant RSD in body mass, the positive allometry indicated a potential for increasing force generation in females than expected for their body mass.…”
Section: Discussionmentioning
confidence: 87%
“…The ratio is greater in mammalivores species: 73% in the red‐tailed hawk ( Buteo jamaicensis calurus ) (Donohue & Dufty, 2006) and 78% in the North American golden eagle ( Aquila chrysaetos canadensis ) (Harmata & Montopoli, 2013). Among piscivorous species, the ratio of male to female body mass is 80% in the white‐tailed sea eagle ( Haliaeetus albicilla ) and 88% in the osprey ( Pandion haliaetus ) (Mosto et al, 2021; Muriel et al, 2010). The intersexual difference in body mass is least in carrion‐eating raptors, with a value of 99% in the griffon vulture ( Gyps fulvus ) and 89% in the bearded vulture ( Gypaetus barbatus ) (Lόpez‐Lόpez et al, 2011; Xirouchakis & Poulakakis, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The raptor pelvis is characterized by a wide and flaring iliac wing in the preacetabular pelvis and a craniocaudally abbreviated postacetabular region. Although the vast majority of work on the raptor hindlimb is focused on the distal limb (e.g., Einoder & Richardson, 2007; Goslow, 1972; Mosto et al, 2021; Ward et al, 2002), it has been observed that raptors commonly extend their entire legs when striking prey (Goslow, 1971). Hip flexors may also play an important role in lifting prey after the strike.…”
Section: Discussionmentioning
confidence: 99%